REVITALISASI PENDIDIKAN GURU DALAM MENJAWAB TANTANGAN ABAD KE-21 - Sari, Cut Kumala; Zahara, Gina Alya; Latifa, Intan (Jurnal Merah Putih Sekolah Dasar, 2025)
The rapid advancement of technology in the 21st century presents significant challenges for the education sector, particularly in improving teacher professionalism at the elementary school level. Teachers are required not only to master subject matter but also to adapt to technological developments and implement innovative learning strategies. However, the integration of technology in elementary education still encounters various obstacles, such as limited infrastructure, unequal access to digital resources, and insufficient teacher competencies, especially in underdeveloped, outermost, and frontier (3T) areas. This study aims to analyze strategies for revitalizing teacher education in response to 21st-century challenges. The research employed a qualitative approach through a literature review by examining relevant scientific articles, journals, and policy documents. The findings indicate that revitalizing teacher education through strengthening professional competencies, integrating educational technology, and implementing supportive government policies can enhance the quality of elementary education. Furthermore, collaboration among teachers, parents, and policymakers is essential to create an inclusive, adaptive, and future-oriented education system. Strengthening teacher professionalism is a key factor in ensuring the sustainability and relevance of education in the digital era.